Sitotoksisitas resin akrilik hybrid setelah penambahan glass fiber dengan metode berbeda (Cytotoxicity of the hybrid acrylic resin after glass fiber reinforcement with difference method) - Intan Nirwana; R. Helal Soekartono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Glass fiber reinforcement of the hybrid acrylic resin with difference method can enhance residual monomer content of the material; it can cause cytotoxic effect on fibroblast cells. The purpose of this study was to know the cytotoxicity of hybrid acrylic resins after glass fiber reinforcement with difference method on the cultured fibroblasts. The squared specimens of 10 mm in length, 10 mm in width and 1.5 mm in thickness were cured for 20 minutes at 100° C. The fibroblast cells were grown in Eagle's Minimum Essential Medium to be 2 × 105 cells/ml, then the cells were added to the samples in the plates and incubated at 37° C. After 48 hours, the cytotoxic effect was determined by direct cell number count using microscope and a hemocytometer. The statistical analyses using one way ANOVA and LSD test showed that there were significant difference in cell viability (p < 0.05) among the groups. The means percentage of cell viability were 90.00%, 99.,11%, 98.66%, it could be concluded that glass fiber reinforcement into hybrid acrylic resin with either first method or second method was not toxic.